Crushed Capsicum chacoense Hunz Fruits: A Food Native Resource of Paraguay with Antioxidant and Anthelmintic Activity - Eva Coronel; Laura Mereles; Silvia Caballero; Nelson Alvarenga (International Journal of Food Science)
The nutritional composition and toxicity of native plants with food potential like Capsicum chacoense are important for the safe use of populations and could be used as a source for searching for new drug candidates. Infections produced by parasites such as helminths are a public health concern for many countries. The drugs used for treating these diseases are few, and the emergence of resistance is a risk. In this work, the nutritional composition, acute toxicity, antioxidant activity, and anthelmintic activity of crushed C. chacoense fruits were evaluated. The composition was analyzed by standard procedures. Antioxidant activity was evaluated using the ABTS radical and the total phenolic compound (TPC) tests. The toxicity was evaluated on Swiss albino mice by the single-DL50-dose procedure. The anthelmintic activity was tested against Eisenia foetida. The samples presented high levels of dietary fiber (47.05-49.19 g/100 g), proteins (14.43-15.60 g/100 g), and potassium (1708-1733 mg/100 g). In the samples, the absence of acute lethal effects in doses lower than 2000 mg/kg was observed. A rich composition of TPC (517.26-543.32 mg GAE/100 g sample), total carotenoids (125.72-239.57 mg/kg), β-carotene (3.29-5.60 mg/kg), and good TAC was observed (154-158 mM TEAC/g SMTC). The methanolic extracts at the doses tested (2.5 to 40 mg/mL) showed good anthelmintic activity. The presence of alkaloids was demonstrated in the methanolic extract, consistent with the levels of capsaicin (131.85 and 98.80 mg/100 g) and dihydrocapsaicin (80.75 and 63.68 mg/100 g), with significant statistical differences between samples (p<0.05). These results show that through the chemical composition of this underutilized native resource and good fruit processing procedures, the C. chacoense fruits have a great nutraceutical potential of interest for the food and pharmaceutical industries.